The effect of a multispecies probiotic on microbiota composition in a clinical trial of patients with diarrhea‐predominant irritable bowel syndrome. Issue 12 (23rd August 2018) - Hod, Keren; Dekel, Roy; Aviv Cohen, Nathaniel; Sperber, Ami; Ron, Yishai; Boaz, Mona; Berliner, Shlomo; Maharshak, Nitsan
Abstract: Background: Although probiotics are increasingly used in irritable bowel syndrome (IBS), their mechanism of action has not been elucidated sufficiently. We aimed to evaluate the impact of a multispecies probiotic on enteric microbiota composition in women with diarrhea‐predominant‐IBS (IBS‐D) and to determine whether these effects are associated with changes in IBS symptoms or inflammatory markers. Methods: In a double‐blind, placebo‐controlled study, Rome III IBS‐D women completed a two‐week run‐in period and eligible women were assigned at random to a probiotic capsule (BIO‐25) or an indistinguishable placebo, twice daily for 8 weeks. IBS symptoms and stool consistency were rated daily by visual analogue scales and the Bristol stool scale. High sensitivity C‐reactive protein, fecal calprotectin and microbial composition were tested at baseline and at 4 and 8 weeks. Microbial sequencing of the 16S rRNA was performed and data were analyzed to compare patients who responded to treatment with those who did not. Key Results: 172 IBS‐D patients were recruited and 107 eligible patients were allocated to the intervention (n = 54) or placebo (n = 53) group. Compared to placebo, BIO‐25 did not result in changes in microbial diversity or taxa proportions, except for higher relative proportions of Lactobacillus in the BIO‐25 group ( P = 0.002). Symptomatic responders to BIO‐25 showed a reduction in the proportion of Bilophila ( P = 0.003) posttreatment. Patients with beneficial inflammatory‐marker changes had higher baseline proportions of Faecalibacterium ( P = 0.03), Leuconostoc ( P = 0.03), and Odoribacter ( P = 0.05) compared to corresponding non‐responders. Conclusions & Inferences: Identifying patients with a more amenable microbiome at treatment initiation may result in better treatment response. Abstract : In this secondary analysis BIO‐25 group did not result in changes in microbial diversity or taxa proportions, except for higher relative proportions of Lactobacillus, compared to placebo. Symptomatic responders to BIO‐25 showed a reduction in the proportion of Bilophila posttreatment. Patients with beneficial inflammatory marker changes had higher baseline proportions of Faecalibacterium, Leuconostoc, and Odoribacter compared to corresponding non‐responders.